2017
DOI: 10.1111/ijcs.12408
|View full text |Cite
|
Sign up to set email alerts
|

Financial literacy among university students: A study in eight European countries

Abstract: This study analysed the level of financial literacy among university students in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
1
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(84 citation statements)
references
References 41 publications
6
46
1
9
Order By: Relevance
“…To summarise, the study reveals low levels of financial knowledge among undergraduate university students in Cyprus. The results broadly concur with the findings of other countries that find gender, parental income and the subject studied at university play an important role in explaining the students' level of financial knowledge (Chen and Volpe, 1998;Cole et al, 2009;Lusardi et al, 2010;Sarigül, 2014;Philippas and Tzora, 2017;Ergün, 2018). Furthermore, financial knowledge is observed to have a distinct and statistically significant channel of influence for sound financial behaviour among students and this channel is not substituted by socio-demographic factors or various skillsets.…”
Section: Econometric Analysis and Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…To summarise, the study reveals low levels of financial knowledge among undergraduate university students in Cyprus. The results broadly concur with the findings of other countries that find gender, parental income and the subject studied at university play an important role in explaining the students' level of financial knowledge (Chen and Volpe, 1998;Cole et al, 2009;Lusardi et al, 2010;Sarigül, 2014;Philippas and Tzora, 2017;Ergün, 2018). Furthermore, financial knowledge is observed to have a distinct and statistically significant channel of influence for sound financial behaviour among students and this channel is not substituted by socio-demographic factors or various skillsets.…”
Section: Econometric Analysis and Resultssupporting
confidence: 89%
“…The results show that Cypriot students have average financial knowledge scores which are below the baseline of 50% in all three variables. Although the financial knowledge scores cannot be strictly compared across countries due to dissimilarities in survey questions and survey designs, it can be observed that the Cypriot students' average financial knowledge scores are comparatively lower than those reported in similar studies from other countries (Demirguc-Kunt et al, 2015;OECD 2016;Philippas and Tzora 2017;Ergün, 2018). Table 3 also depicts the summary statistics of the variables used in the regression analysis over the entire sample, the sample of highly knowledgeable students (i.e., at least 4 correct answers, FK_DUMMY = 1), and the sample of less knowledgeable students (i.e., fewer than 4 correct answers, FK_DUMMY = 0).…”
Section: Descriptive Analysismentioning
confidence: 85%
See 1 more Smart Citation
“…While considerable research literature on young adults exists including the topics on income (Black, Devereux, & Salvanes, ), assets (Letkiewicz & Fox, ), credit card overspending (Sotiropoulos & D'Astous, ), financial literacy (Ergün, ; Lusardi, Mitchell, & Curto, ) and financial behaviours (Friedline, Elliott, & Nam, ; Tang, ; Tang, Baker, & Peter, ), the financial independence of young adults, an important topic of transition to adulthood (Shim, Serido, Bosch, & Tang, ) remains underexplored. Without financial independence, young adults have to rely on either social welfare or parental support.…”
Section: Introductionmentioning
confidence: 99%
“…Financial courses in the educational programs of many universities might help the students to handle their financial matters better and to improve their financial welfare (Ergün, 2017). Ali et al (2004) explained that Customer Education programs might help young people with the skills that they have been equipped with in order to make their financial decisions.…”
Section: The Implementation Of Life Valuesmentioning
confidence: 99%